Drinking to thirst versus drinking ad libitum during road cycling - Armstrong, L. E.; Johnson, E. C.; Kunces, L. J.; Ganio, M. S.; Judelson, D. A.; Kupchak, B. R.; Vingren, J. L.; Munoz, C. X.; Huggins, R. A.; Hydren, J. R.; Moyen, N. E.; Williamson, K. H. (Journal of Athletic Training, 2015)
Context: The sensation of thirst is different from the complex behavior of drinking ad libitum. Rehydration recommendations to athletes differ, depending on the source, yet no previous researchers have systematically compared drinking to thirst (DTT) versus ad libitum drinking behavior (DAL).